(xy)dx+(x+1)dy=0

Simple and best practice solution for (xy)dx+(x+1)dy=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (xy)dx+(x+1)dy=0 equation:


Simplifying
(xy) * dx + (x + 1) * dy = 0

Multiply xy * dx
dx2y + (x + 1) * dy = 0

Reorder the terms:
dx2y + (1 + x) * dy = 0

Reorder the terms for easier multiplication:
dx2y + dy(1 + x) = 0
dx2y + (1 * dy + x * dy) = 0

Reorder the terms:
dx2y + (dxy + 1dy) = 0
dx2y + (dxy + 1dy) = 0

Reorder the terms:
dxy + dx2y + 1dy = 0

Solving
dxy + dx2y + 1dy = 0

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Factor out the Greatest Common Factor (GCF), 'dy'.
dy(x + x2 + 1) = 0

Subproblem 1

Set the factor 'dy' equal to zero and attempt to solve: Simplifying dy = 0 Solving dy = 0 Move all terms containing d to the left, all other terms to the right. Simplifying dy = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(x + x2 + 1)' equal to zero and attempt to solve: Simplifying x + x2 + 1 = 0 Reorder the terms: 1 + x + x2 = 0 Solving 1 + x + x2 = 0 Move all terms containing d to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + x + -1 + x2 = 0 + -1 Reorder the terms: 1 + -1 + x + x2 = 0 + -1 Combine like terms: 1 + -1 = 0 0 + x + x2 = 0 + -1 x + x2 = 0 + -1 Combine like terms: 0 + -1 = -1 x + x2 = -1 Add '-1x' to each side of the equation. x + -1x + x2 = -1 + -1x Combine like terms: x + -1x = 0 0 + x2 = -1 + -1x x2 = -1 + -1x Add '-1x2' to each side of the equation. x2 + -1x2 = -1 + -1x + -1x2 Combine like terms: x2 + -1x2 = 0 0 = -1 + -1x + -1x2 Simplifying 0 = -1 + -1x + -1x2 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 0.95x+0.05(2-x)=0.10(163) | | 4z^2-4x=24 | | 12 = k2 + 10 | | 72x^2-8x+9=0 | | 3.5+(-7.5)= | | -1-6p=6-7p | | n-9-9n=1-7n | | 7=2g+3 | | 6+6n=-4(2-5n) | | 3.5+(7.5)= | | 28-6x=49-9x | | (X+1)=x | | 14y+41=139 | | 0.33333333333(21-3a)=6-a | | 3x+2x-11=84 | | 6x+0.4=6.4 | | -2x-18=-(1-2x)+4x | | 4(a+2)=14-2(3-a) | | 4n=5-5n | | 88=12x-44 | | 16x-16-8x-12=3 | | 9-4b=4-3b-6b | | 16-(2x-3)=6 | | 6x-14=2(3x-72) | | 11x-13=5(2x+4)-7 | | 45=29-2(x-3) | | 2x^2-y^2-8x+6y-2=0 | | 8a+10=50 | | 7+7k=8k+2 | | -6m+3m=4-m | | 1000=20x+100y | | nsquared+n-105=0 |

Equations solver categories